A rare cause of dyspepsia: a case report of gastric diverticulum - Ren, Yi Kow; Ismail, Dhauiddin Hai; Chooi, Leng Low; Md Saad, Khatrulnada; Mor Japar Khan, Ed Simor Khan (Kulliyyah of Medicine, International Islamic University Malaysia, 2019)
A gastric diverticulum is an outpouching from the gastric mucosa. It is extremely rare. It is normally asymptomatic, but some may present with non-specific abdominal pain. A combination of upper gastrointestinal endoscopy and radiological contrast study such as oral barium study and computed tomography are needed to make a definite diagnosis and to rule out other associated pathology. Although treatment with medical therapy has been reported to be effective, the use of open and laparoscopic resection also yields a good outcome in the management of complicated gastric diverticulum. We present a case of symptomatic gastric diverticulum which has been successfully treated with medical therapy.